Manajemen Perguruan Tinggi Berbasis Pesantren - Jaudi, Jaudi (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
The management of pesantren-based higher education institutions in Indonesia faces various challenges in balancing Islamic values with modern academic demands. Pesantren-based universities have a unique potential to develop an educational model rooted in pesantren values while also meeting higher education standards. This study aims to analyze how the management model of pesantren-based universities can be optimized to remain relevant and competitive. The research uses a descriptive qualitative method with data collection through a literature review, providing insights into ideal management practices in this context. The results indicate that the success of pesantren-based university management is greatly influenced by the integration of pesantren values within a professional management system, particularly in areas such as human resource management, curriculum development, and community engagement. This research contributes by offering adaptive, value-based management recommendations, providing a reference for sustainable and innovative management of pesantren-based higher education institutions.